The Effect of Price Advertising on Prices: Evidence in the Wake of 44 Liquormart - Milyo, Jeffrey; Waldfogel, Joel (American Economic Review, 1999)
The 44 Liquormart decision, eliminating Rhode Island's ban on liquor price advertising, made Rhode Island the subject of a natural experiment for measuring the effect of advertising on prices. Using Massachusetts prices as controls, we find that advertising stores substantially cut only prices of the products that they advertise. Prices of other products, at both advertising and nonadvertising stores, do not change. Advertising stores cut their prices on products advertised by rivals, while nonadvertising stores do not. We find no reductions in price dispersion across stores. Newspaper-advertising stores appear to draw a higher share of customers after they advertise. (JEL L11, L51, L66)